"The Wellbeing of Women in Entrepreneurship. A Global Perspective". Editorial Routledge, 219, 420 páginas. Lepeley, M.T.; Kuschel, K.; Beutell, N.; Pouw, N.; Eijdenberg, E.L. (Eds.) - María Asunción Prats Albentosa (Revista de Economía Mundial, 2020)
Reseña del libro:"The Wellbeing of Women in Entrepreneurship. A Global Perspective"Lepeley, M.T.; Kuschel, K.; Beutell, N.; Pouw, N.; Eijdenberg, E.L. (Eds.)Editorial Routledge, 2019, 420 páginas.